Evaluation of the interaction between environmental factors, cultivation and fertilisation - Sedlák, Gergő (Acta Agraria Debreceniensis, 2012)
The effect of production factors on maize yield was examined in the Látókép Experiment Site of the Centre of Agricultural and Applied Economic Sciences of the University of Debrecen on calcareous chernozem soil between 2001 and 2003. The impact of environmental factors (precipitation, temperature, number of sunny hours), cultivation methods (autumn ploughing, spring shallow cultivation) and fertilisation (non-fertilised, 120 kg N + 90 kg P2O5 + 106 kg K2O, and 240 kg N + 180 kg P2O5 + 212 kg K2O) on maize yield was examined. During the three years, autumin ploughing significantly increased yield by 2.91 t ha-1 in comparison with spring shallow cultivation. The yield increasing effect of fertilisation was observed in each year, although its extent depended on the given crop year and the applied cultivation method. The higher fertiliser dose (240 kg N ha-1) did not cause significantly higher yield in either year. After the evaluation of the observed correlations, it can be established that the yield increasing effect of fertilisation was higher in the case of autumn ploughing in comparison with spring shallow cultivation. The environmental factors (especially the extent of precipitation) significantly affected the maize yield.